The Influence of Electronic Word of Mouth, Perceived Ease of Use, and Digital Marketing on the Usage Decision of Duolingo Application Among Generation Z in Surabaya City - Bimo Dwi Pasa; Budi Prabowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to identify and analyze the influence of Electronic Word of Mouth, Perceived Ease of Use, and Digital Marketing on the Decision to use the Duolingo application among Generation Z in Surabaya City. The study is grounded in the urgency of technological development, particularly in educational-based applications, which must align with user behavior. The sampling technique employed was non-probability sampling with a purposive sampling method, involving a total of 160 respondents. This research applied a quantitative approach using multiple linear regression analysis, with data processed through SPSS version 25. The results indicate that Electronic Word of Mouth, Perceived Ease of Use, and Digital Marketing simultaneously have a positive and significant effect on Usage Decision. Partially, each independent variable also shows a significant influence on the dependent variable. The coefficient of determination (R²) value of 0.650 indicates that 65% of the variation in Usage Decision is explained by the three independent variables in this study, while the remaining 35% is influenced by other factors outside the model.